Possibilities of Developing Study Motivation in E-Learning Products - Dumčienė, A.; Lapėnienė, D. (Elektronika ir Elektrotechnika, 2010)
The aim of the paper is to assess the quality of e-learning products developed in colleges for mixed learning in terms of value attitudes and learning motivation development. Regarding the aspect of value development, nine groups of criteria were employed while ARCS Model by J.M.Keller was used for the assessment of educational opportunities. 10 experts and 122 students provided the evaluations. In terms of eleven criteria, the average evaluations of the experts and the students differed statistically significantly (p<0.05) while opinions did not differ regarding the criteria of confidence and satisfaction (p>0.05).